Promotion: Turnover and Preemptive Wage Offers - Dan Bernhardt; David Scoones (Queen's University, Department of Economics, 1991)
This paper examines the strategic promotion and wage decisions of employers when employees may be more valuable to competing firms, even in the presence of firm specific human capital. Competing employers must incur a cost to learn the quality of their match with a manager. Because promotion signal that workers are potentially valuable managers in other firms, it can induce turnover. To preempt competition for a promoted worker, an employer may offer a wage so high that it discourages competitors from acquiring information and bidding up the wage further or hiring the worker away. Also, to avoid competition, employers will fail to promote some less well-matched workers who should be promoted.
Keywords: 330